2007
DOI: 10.1002/qua.21520
|View full text |Cite
|
Sign up to set email alerts
|

The N‐particle wave function as a homogeneous functional of the density

Abstract: ABSTRACT:It is shown that requiring consistency with the structure of the equation that determines the wave function associated to a density ͑r ៝͒ by density-functional theory, yields the N-particle wave function as a degree-half homogeneous functional of the density, and leads to a separation A͓N, ͔ of N dependence (with N ϭ ͵ ͑r ៝͒ dr ៝) of density functionals A͓͔ ϭ A͓ ͵ , ͔ for which A͓ ͵ , ͔ ϭ A͓ ͵ , ͔; as a consequence of the linearity of quantum mechanical operators. This implies that the ground-state va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…(54) It is worth noting that requiring N-particle density functionals to be homogeneous of some degree eliminates the ambiguity present in their definition [15], meaning that the only possible N-particle noninteracting kinetic-energy and exchangeenergy density functionals homogeneous of degree one and two, respectively, are those constructed in [14] and here (see also the Appendix). Finally, the question of separability [41] for N-particle density functionals may be worth taking a look at, referring also to a recent work [42], which investigates the separability problem of (explicitly) N-dependent density functionals.…”
Section: It Is Known Thatmentioning
confidence: 99%
See 3 more Smart Citations
“…(54) It is worth noting that requiring N-particle density functionals to be homogeneous of some degree eliminates the ambiguity present in their definition [15], meaning that the only possible N-particle noninteracting kinetic-energy and exchangeenergy density functionals homogeneous of degree one and two, respectively, are those constructed in [14] and here (see also the Appendix). Finally, the question of separability [41] for N-particle density functionals may be worth taking a look at, referring also to a recent work [42], which investigates the separability problem of (explicitly) N-dependent density functionals.…”
Section: It Is Known Thatmentioning
confidence: 99%
“…which, for a ρ( ) v r , gives the minimum of the sum T (15) over the set of normalized Slater determinants (ψ D ) that yield ρ( ) v r , that is,…”
Section: The Hartree-fock-kohn-sham Scheme and The Kohn-sham Formulat...mentioning
confidence: 99%
See 2 more Smart Citations
“…for the CWB ground-state density. It can be observed that rewriting equation (11) in the form h2 16m ρ (r) + h2 8m…”
mentioning
confidence: 99%